Test systems «tropT sensitive»: experience of use at intensive therapy unit, city clinical hospital - A. A. Kotlyarov; M. Z. Chukarov; D. A. Amelkin; R. A. Choudri Mukhammad; A. A. Aleksandrovsky (Российский кардиологический журнал, 2005)
.